1976
DOI: 10.1139/v76-160
|View full text |Cite
|
Sign up to set email alerts
|

Urea – boron trihalide adducts. IV. Ionic–covalent equilibria in the tetramethylthiourea–BF3 and tetramethylselenourea–BF3 systems and the influence of B2F7 formation

Abstract: . 54,1121 (1976). Tetramethylthiourea and tetramethylselenourea form 1 :I BF3 adducts which are partially converted to ionic structures (donor)2BF2+.BF4-in solution. The degree of ionization is small except at low temperatures when BF3 is in excess; ionization is essentially complete at -90 "C when a sultcient excess of BF3 is present. Formation of B2F7-from BF4-and BF3 at low temperatures is responsible for this. Hence under these conditions the 1 :1 adduct is replaced by (donor)2BF2+.B2F7-. The existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This inspired us to look for additives, which could promote the borylation reaction further. Considering that formation of borocations in benzene cannot be completely excluded (Scheme 3), we turned out attention to tetramethylthiourea (TMTU) that proved assisting the autoionization of BF 3 [17] . Accordingly, we found that the addition of small (5 mol %) amounts TMTU ( 5 a ) to both BF 3 ⋅SMe 2 / 4 a and BF 3 ⋅SMe 2 / 4 d pairs increases the rate of 2 a formation (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…This inspired us to look for additives, which could promote the borylation reaction further. Considering that formation of borocations in benzene cannot be completely excluded (Scheme 3), we turned out attention to tetramethylthiourea (TMTU) that proved assisting the autoionization of BF 3 [17] . Accordingly, we found that the addition of small (5 mol %) amounts TMTU ( 5 a ) to both BF 3 ⋅SMe 2 / 4 a and BF 3 ⋅SMe 2 / 4 d pairs increases the rate of 2 a formation (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…B(C 6 F 5 ) 3 (B). To the best of our knowledge, only two examples of Lewis pairs between a CQSe moiety and boron have been characterized, 27,33 of which only one at the solid state. Here, we suspended an equimolar amount of B and 1 in n-pentane, obtaining a solid, which was recrystallized from CH 2 Cl 2 /n-pentane.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The C-N bond of selenoamides has been known to be partially double since 1969. 30 This implies that the C-Se bond is also partially double and, indeed, its length can be influenced by the coordination of CQSe to a metal center 29,31 (even if not all the metals have an appreciable effect 32 ) or a boron trihalide 33 and, by weaker secondary interactions, as hydrogen bonding. 34 Therefore, it can be supposed that DH ‡ r will vary in the presence of different Lewis acids (LAs).…”
Section: Introductionmentioning
confidence: 99%